1958
DOI: 10.1055/s-0028-1114156
|View full text |Cite
|
Sign up to set email alerts
|

Das gewerbliche Asthma1

Abstract: Betrachtet man unter gewerbemedizinischen Gesichtspunkten die Probleme, die mit dem rein symptomatischen Krankheitsbegriff Asthma bronchiale" -wie auch ihm verwandten Störungen, insbesondere der asthmoiden Bronchitis (1, 2) -verknüpft sind, so erhebt sich die Frage: Läßt sich der Nachweis erbringen, daß eine spezielle berufliche Tätigkeit als Anlaß sowohl für die Entstehung wie auch für die weitere Entwicklung asthmatischer Störungen verantwortlich zumachen ist? Mit anderen Worten: Gibt es außer den bisher bek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Experiments described in this communication clearly implicate IgE antibodies in the asthmatic response observed in a laboratory employee engaged in the rearing of large numbers of blowflies. Such reactions are known to occur in individuals involved in the breeding of some other insect species [1][2][3][4][5]17] and allergic reactions to the American screw-worm fly (C, hominivorax), a species in the same sub-family as C. bezziana, the screw-worm fly studies here, have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments described in this communication clearly implicate IgE antibodies in the asthmatic response observed in a laboratory employee engaged in the rearing of large numbers of blowflies. Such reactions are known to occur in individuals involved in the breeding of some other insect species [1][2][3][4][5]17] and allergic reactions to the American screw-worm fly (C, hominivorax), a species in the same sub-family as C. bezziana, the screw-worm fly studies here, have been described.…”
Section: Discussionmentioning
confidence: 99%
“…A number of the published reports deal with insect species that were being reared and studied because they are pests [1]. Sensitization following occupational exposure has provided clear evidence ofthe involvement of insects in inhalant allergies and has demonstrated that insects may be the source of some extremely potent allergens that afl'ect a high proportion of workers [1][2][3][4][5]. Severe allergic manifestations were observed among persons involved in the distribution of adults ofthe American screw-worm fly.…”
Section: Introductionmentioning
confidence: 99%